2021
DOI: 10.2337/dbi20-0046
|View full text |Cite
|
Sign up to set email alerts
|

From Pancreatic β-Cell Gene Networks to Novel Therapies for Type 1 Diabetes

Abstract: Completion of the Human Genome Project enabled a novel systems- and network-level understanding of biology, but this remains to be applied for understanding the pathogenesis of type 1 diabetes (T1D). We propose that defining the key gene regulatory networks that drive β-cell dysfunction and death in T1D might enable the design of therapies that target the core disease mechanism, namely, the progressive loss of pancreatic β-cells. Indeed, many successful drugs do not directly target individual disease genes but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 75 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…Recent evidence suggests that stress pathways triggered within β cells initiate and/or accelerate autoimmune β cell destruction ( 3 , 5 ). Multiple layers of evidence implicate interferon α (IFNα) signaling as a key component of the early stages of T1D pathophysiology ( 6 ). Type I IFN is expressed in pancreatic islets from people with T1D, and islets obtained from living donors with recent-onset T1D show an IFN-stimulated gene signature ( 3 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that stress pathways triggered within β cells initiate and/or accelerate autoimmune β cell destruction ( 3 , 5 ). Multiple layers of evidence implicate interferon α (IFNα) signaling as a key component of the early stages of T1D pathophysiology ( 6 ). Type I IFN is expressed in pancreatic islets from people with T1D, and islets obtained from living donors with recent-onset T1D show an IFN-stimulated gene signature ( 3 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of isogenic hESC platforms and patient-derived iPSCs to survey the genetics of T1D at multiple cellular levels has been suggested in the literature [ 250 , 251 , 252 ]. Studies with patient-derived stem cells to model T1D include examples such as: the use of iPSC-derived SC-β to evaluate their response to cytokines [ 253 , 254 ], generation of iPSC-derived APCs to model their interaction with T cells [ 255 ] or complex autologous platforms with iPSC-derived SC-β and immune cells from the same patients [ 256 ].…”
Section: Genetic Basis Of β Cell Dysfunctionmentioning
confidence: 99%
“…Others have also probed the response of iPSC-derived SC-β to cytokines [ 253 , 254 ] or study their interaction with immune cells in complex isogenic systems [ 257 ]. The use of gene-editing techniques on iPSC/hESC to study T1D-predisposing SNPs in response to cytokines or interaction with immune cells is an approach that has already been considered [ 251 ]. Several other studies have focused on the influence of genetic variants on β cell ER stress.…”
Section: Classification Of Processes Associated With β Cell Dysfunctionmentioning
confidence: 99%
“…Several studies reported the prominent role of IFNα in the induction of autoimmunity in T1D (23). Since TYK2 is important for the IFN-I signaling mediated through IFNAR1, we took advantage of our TYK2 KO model to understand its role during the dialogue between IFNα and the developing pancreatic islet cells.…”
Section: Tyk2 Regulates the Ifnα Response In Sc-isletsmentioning
confidence: 99%